Silicon-carbon material with multi-layer coating structure and preparation method and application of silicon-carbon material
By performing multi-layer carbon coating on the porous carbon core and adding conductive nanocarbon fillers, the structural instability problem caused by volume expansion during lithiation of silicon anode materials is solved, and the specific capacity and cycling performance of lithium-ion battery anode materials are significantly improved.
Patent Information
- Application Number
- CN202510162065.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The volume expansion of the silicon negative electrode material during the lithiation process leads to cracking, crushing or falling off, destroying the SEI film, significantly reducing the cycle life. The specific capacity of the existing silicon carbon negative electrode material is relatively low, limiting its wide application in lithium-ion batteries.
Silicon carbon material with a multi-layer clad structure is used to coat the first and second layers of carbon on the porous carbon core body, and conductive nanocarbon fillers are incorporated into the second carbon layer to form a three-dimensional electron transmission network to improve the conductivity and structural stability.
The specific capacity, coulomb efficiency and cyclic performance of silicon carbon materials have been significantly improved. The first reversible capacity reaches 1882~2071mAh/g, the first Coulomb efficiency is 92.6~94.1%, and the cyclic capacity retention rate of 100 cycles is 95.3~97.7%.
Smart Images

Figure CN119627090A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a silicon-carbon material with a multi-layer coating structure and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are ideal power sources for portable electronic devices, electric vehicles, and energy storage systems. The development of electrode materials with high specific energy is the core content of lithium-ion battery research. Silicon anode materials have extremely high theoretical specific capacity (4200mAh / g) and are expected to replace graphite as the anode material for the next generation of lithium-ion batteries. However, there are still huge challenges in the practical application of silicon anodes. During the lithiation process, silicon materials will undergo volume expansion, causing cracking, crushing, or falling off from the current collector, destroying the original SEI film (i.e., solid electrolyte interface film) and contacting with the electrolyte to form a new SEI film, thereby significantly reducing the cycle life. Therefore, silicon anode materials usually need to be carbon-coated to form silicon-carbon composite materials to improve their conductivity and inhibit the volume expansion effect. However, the current specific capacity of silicon-carbon anode materials is low, which limits their widespread application in lithium-ion batteries. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a multi-layer coated silicon-carbon material and its preparation method and application. The multi-layer coated silicon-carbon material provided by the present invention has excellent specific capacity, coulombic efficiency and cycle performance as a negative electrode material for lithium-ion batteries.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a silicon-carbon material with a multi-layer coating structure, comprising a porous carbon core body, a first carbon layer and a second carbon layer coating the porous carbon core body in sequence from the inside to the outside, the porous carbon core body comprising porous carbon and nano-silicon particles deposited on the surface and in the pores of the porous carbon, the pores of the porous carbon comprising micropores; and conductive nano-carbon fillers are dispersed in the second carbon layer.
[0005] Preferably, the porous carbon comprises one or more of biomass-based porous carbon, resin-based porous carbon and asphalt-based porous carbon; the specific surface area of the porous carbon is 700-1900 m 2 / g, average pore size is 0.5~5nm, D 50 The particle size is 2~15μm.
[0006] Preferably, the thickness of the first carbon layer is 10-500 nm; the thickness of the second carbon layer is 20-500 nm.
[0007] Preferably, the particle size of the nano silicon particles is 2-10 nm; the mass of the nano silicon particles is 30-70% of the total mass of the porous carbon core and the first carbon layer.
[0008] Preferably, the conductive nano-carbon filler includes one or more of graphene, carbon nanotubes, nano-carbon black and nano-carbon fibers; and the mass content of the conductive nano-carbon filler in the second carbon layer is 3-15%.
[0009] Preferably, the specific surface area of the silicon-carbon material of the multi-layer coating structure is less than 5.5 m 2 / g.
[0010] The present invention provides a method for preparing a silicon-carbon material with a multilayer coating structure as described in the above technical solution, comprising the following steps: The porous carbon is subjected to a first chemical vapor deposition under the condition of introducing a silicon source gas and a first inert gas, so as to form nano silicon particles on the surface and in the pores of the porous carbon, thereby obtaining the porous carbon core; the temperature of the first chemical vapor deposition is 300-550° C.; The porous carbon core body is subjected to a second chemical vapor deposition under the condition of introducing a carbon source gas and a second inert gas, so as to form a first carbon layer on the surface of the porous carbon core body to obtain a primary carbon-coated silicon-carbon material; the temperature of the second chemical vapor deposition is 450-750° C.; The primary carbon-coated silicon-carbon material is mixed with a resin dispersion, and the solvent is removed and carbonized in sequence to form a second carbon layer on the outer surface of the first carbon layer to obtain the silicon-carbon material with a multi-layer coating structure; the resin dispersion includes a resin, a conductive nano-carbon filler and a dispersant.
[0011] Preferably, the silicon source gas includes one or more of monosilane, disilane, trisilane, butasilane and dichlorosilane, and the flow rate of the silicon source gas is 1~15L / min; the first inert gas includes nitrogen and / or argon, and the flow rate of the first inert gas is 1~30L / min.
[0012] Preferably, the carbon source gas includes one or more of methane, ethane, propane, cyclohexane, ethylene, propylene and acetylene, and the flow rate of the carbon source gas is 0.5~5L / min; the second inert gas includes nitrogen and / or argon, and the flow rate of the second inert gas is 1~20L / min.
[0013] The present invention provides the use of the silicon-carbon material with a multi-layer coating structure described in the above technical solution or the silicon-carbon material with a multi-layer coating structure prepared by the preparation method described in the above technical solution as a negative electrode active material in a lithium ion battery.
[0014] The present invention provides a silicon-carbon material with a multi-layer coating structure. Compared with the prior art, the present invention has the following beneficial effects: In the present invention, silicon particles are deposited in the porous carbon and the silicon particles are nano-sized, having more lithium insertion / delithiation sites. The micropores of the porous carbon provide deposition space and volume expansion buffer space for the silicon particles. This structure is conducive to increasing the loading capacity of silicon nanoparticles and structural stability. The present invention coats the porous carbon with a first carbon layer and a second carbon layer, which can further reduce the specific surface area, and at the same time appropriately increase the thickness of the carbon coating layer, reduce the direct contact between silicon and the electrolyte, and is beneficial to improve the initial coulombic efficiency and cycle stability; The present invention adds conductive nano-carbon fillers into the second carbon layer to form a three-dimensional electron transmission network, further improve the conductivity of the carbon coating layer, and reduce interface impedance and polarization effect.
[0015] The multi-layer coated silicon-carbon material provided by the present invention has excellent specific capacity, coulombic efficiency and cycle performance as a negative electrode active material for lithium-ion batteries. The results of the embodiment show that the multi-layer coated silicon-carbon material provided by the present invention is applied to lithium-ion batteries as a negative electrode active material, and the first reversible capacity is 1882~2071mAh / g, the first coulombic efficiency is 92.6~94.1%, and the 100-cycle cycle capacity retention rate is 95.3~97.7%.
[0016] The present invention provides a method for preparing a silicon-carbon material with a multilayer coating structure as described in the above technical solution. The present invention uses porous carbon as a matrix to obtain a primary carbon-coated silicon-carbon material by a vapor deposition method; and uses a liquid phase mixing method to perform secondary carbon coating using a resin as a precursor. The present invention combines a high-density vapor coating process with a low-cost liquid coating process to achieve uniform deposition of nano-silicon on a porous carbon matrix and double-layer carbon coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a scanning electron microscope photo of the silicon-carbon material with a multilayer coating structure in Example 1; Figure 2 The cycle specific capacity curve of the lithium-ion battery assembled with the silicon-carbon material of the multi-layer coating structure in Example 1; Figure 3 This is the charge and discharge curve of the lithium-ion battery assembled with the silicon-carbon material with a multi-layer coating structure in Example 1. DETAILED DESCRIPTION
[0018] The present invention provides a silicon-carbon material with a multi-layer coating structure, comprising a porous carbon core body, a first carbon layer and a second carbon layer coating the porous carbon core body in sequence from the inside to the outside, the porous carbon core body comprising porous carbon and nano-silicon particles deposited on the surface and in the pores of the porous carbon, the pores of the porous carbon comprising micropores; and conductive nano-carbon fillers are dispersed in the second carbon layer.
[0019] The silicon-carbon material with a multilayer coating structure provided by the present invention comprises a porous carbon core, wherein the porous carbon core comprises porous carbon and nano-silicon particles deposited on the surface and in the pores of the porous carbon. In the present invention, the pores of the porous carbon comprise micropores; the porous carbon preferably comprises one or more of biomass-based porous carbon, resin-based porous carbon and asphalt-based porous carbon; the specific surface area of the porous carbon is preferably 700-1900 m 2 / g, more preferably 900~1500m 2 / g, more preferably 1200~1400m 2 / g, the average pore size is preferably 0.5 to 5 nm, more preferably 1.5 to 3 nm, and further preferably 2 to 2.5 nm, D 50 The particle size is preferably 2~15μm, more preferably 5~10μm, and further preferably 6~8μm. The present invention has no special requirements on the source of the porous carbon. It can be prepared by commercial products or by methods well known to those skilled in the art, so as to meet the requirements of specific surface area, average pore size and particle size. In the present invention, the particle size of the nano silicon particles is preferably 2~10nm, which can be 2, 3, 4, 5, 6, 7, 8, 9 or 10nm. In the present invention, the silicon particles deposited in the porous carbon are of adjustable nano size and have more lithium insertion / delithiation sites. The micropores of the porous carbon provide deposition space and buffer space for volume expansion for the silicon particles.
[0020] The silicon-carbon material of the multilayer coating structure provided by the present invention includes a first carbon layer and a second carbon layer that sequentially coat the porous carbon core from the inside to the outside. In the present invention, the thickness of the first carbon layer is preferably 10~500nm, more preferably 30~200nm, and further preferably 35~100nm; the thickness of the second carbon layer is preferably 20~500nm, more preferably 50~200nm, and further preferably 90~190nm. The present invention controls the coating thickness of the first carbon layer and the second carbon layer within an appropriate range. If the thickness of the carbon layer is too small, the volume expansion of the silicon particles cannot be suppressed, and it is easy to break, resulting in a decrease in the cycle stability of the silicon-carbon material; if the thickness of the carbon layer is too large, the ion migration resistance will be increased and the silicon content will be reduced, resulting in a decrease in the capacity and rate performance of the silicon-carbon material. In the present invention, the mass of the nano-silicon particles is preferably 30~70% of the total mass of the porous carbon core and the first carbon layer (the rest is carbon), more preferably 40~65%, and further preferably 45~62%. In the present invention, conductive nano-carbon fillers are dispersed in the second carbon layer, and the conductive nano-carbon fillers preferably include one or more of graphene, carbon nanotubes, nano-carbon black and nano-carbon fibers; the mass content of the conductive nano-carbon fillers in the second carbon layer is preferably 3-15%. The present invention coats the porous carbon with the first carbon layer and the second carbon layer, which can reduce the specific surface area, and at the same time appropriately increase the thickness of the carbon coating layer, reduce the direct contact between silicon and electrolyte, and is conducive to improving the first coulomb efficiency and cycle stability; and the present invention incorporates conductive nano-carbon fillers into the second carbon layer, which can form a three-dimensional electron transport network, further improve the conductivity of the carbon coating layer, and reduce the interface impedance and polarization effect.
[0021] In the present invention, the D of the silicon-carbon material of the multilayer coating structure 50 The particle size is preferably 1-15 μm, more preferably 6-9 μm, and the specific surface area is preferably <5.5 m 2 / g, more preferably 3 to 5 m 2 / g.
[0022] The present invention provides a method for preparing a silicon-carbon material with a multilayer coating structure as described in the above technical solution, comprising the following steps: The porous carbon is subjected to a first chemical vapor deposition under the condition of introducing a silicon source gas and a first inert gas, so as to form nano silicon particles on the surface and in the pores of the porous carbon, thereby obtaining the porous carbon core body; the temperature of the first vapor deposition is 300-550° C.; The porous carbon core body is subjected to a second chemical vapor deposition under the condition of introducing a carbon source gas and a second inert gas, so as to form a first carbon layer on the surface of the porous carbon core body to obtain a primary carbon-coated silicon-carbon material; the temperature of the second chemical vapor deposition is 450-750° C.; The primary carbon-coated silicon-carbon material is mixed with a resin dispersion, and the solvent is removed and carbonized in sequence to form a second carbon layer on the outer surface of the first carbon layer to obtain the silicon-carbon material with a multi-layer coating structure; the resin dispersion includes a resin, a conductive nano-carbon filler and a dispersant.
[0023] In the present invention, unless otherwise specified, all raw materials involved are commercially available products.
[0024] The present invention conducts a first chemical vapor deposition on porous carbon under the condition of introducing a silicon source gas and a first inert gas, forms nano silicon particles on the surface and in the pores of the porous carbon, and obtains the porous carbon core. In the present invention, the porous carbon is the same as the above-mentioned technical solution, which will not be repeated here; the porous carbon has a high specific surface area, a small particle size, sufficient vapor deposition, and a high silicon content, so that the capacity of the silicon-carbon material is high. In the present invention, the silicon source gas preferably includes one or more of monosilane, disilane, trisilane, butadisilane and dichlorosilane, and the flow rate of the silicon source gas is preferably 1~15L / min, more preferably 3~10L / min; the first inert gas preferably includes nitrogen and / or argon, and the flow rate of the first inert gas is preferably 1~30L / min, more preferably 10~25L / min. In the present invention, the temperature of the first chemical vapor deposition is preferably 300-550°C, more preferably 450-550°C, and the holding time is preferably 1-10h, more preferably 5-6h. The present invention preferably places the porous carbon in a reactor, and after the temperature is raised to 300-550°C, a mixed gas of a silicon source gas and a first inert gas is introduced, and the first chemical vapor deposition is carried out at a temperature of 300-550°C; the reactor is preferably a high-temperature rotary furnace or a fluidized bed. After the first chemical vapor deposition, nano-silicon particles are deposited on the surface and in the pores of the porous carbon to form the porous carbon core.
[0025] After obtaining the porous carbon core body, the present invention conducts a second chemical vapor deposition on the porous carbon core body under the condition of introducing a carbon source gas and a second inert gas, forms a first carbon layer on the surface of the porous carbon core body, and obtains a primary carbon-coated silicon-carbon material. In the present invention, the carbon source gas preferably includes one or more of methane, ethane, propane, cyclohexane, ethylene, propylene and acetylene, and the flow rate of the carbon source gas is preferably 0.5~5L / min, more preferably 1~2L / min; the second inert gas preferably includes nitrogen and / or argon, and the flow rate of the second inert gas is preferably 1~20L / min, more preferably 5~15L / min. In the present invention, the temperature of the second chemical vapor deposition is preferably 450~750℃, more preferably 550~650, and the insulation time is preferably 1~10h, more preferably 4~6h. In the present invention, the porous carbon core body is preferably heated to 450-750°C, and then a mixed gas of a carbon source gas and a second inert gas is introduced, and the second chemical vapor deposition is performed while maintaining the temperature. After the second chemical vapor deposition, a first carbon layer is coated on the surface of the porous carbon core body to form a primary carbon-coated silicon-carbon material.
[0026] After obtaining the primary carbon-coated silicon-carbon material, the present invention mixes the primary carbon-coated silicon-carbon material with a resin dispersion, removes the solvent and carbonizes in sequence, forms a second carbon layer on the outer surface of the first carbon layer, and obtains the silicon-carbon material with the multi-layer coating structure. In the present invention, the resin dispersion includes a resin, a conductive nano-carbon filler and a dispersant; the resin preferably includes one or more of urea-formaldehyde resin, pyrimidine resin, phenolic resin, melamine resin, furfuryl alcohol resin, polyurethane and epoxy resin; the conductive nano-carbon filler is the same as the above technical solution and will not be repeated here; the dispersant preferably includes one or more of water, ethanol, isopropanol, acetone, toluene, tetrahydrofuran, dimethylformamide and dimethyl sulfoxide. In the present invention, the mass fraction of the resin in the resin dispersion is preferably 1.5-15%, more preferably 4-10%, and further preferably 7-8%, and the mass fraction of the conductive nano-carbon filler is preferably 0.1-1.0%, more preferably 0.4-0.7%, and further preferably 0.4-0.5%; the mass ratio of the primary carbon-coated silicon-carbon material to the resin dispersion is preferably 1:1-1:5, and more preferably 1:2-1:4. In the present invention, the mixing is preferably stirring mixing, and the stirring rate of the stirring mixing is preferably 200-1200rpm, and more preferably 500-1000rpm, and the stirring time is preferably 3-20h, and more preferably 6-15h.
[0027] In the present invention, the solvent removal method is preferably heating evaporation or freeze drying, the heating evaporation temperature is preferably 60~200℃, and the time is preferably 1~20h; the freeze drying temperature is preferably -20℃~-70℃, and the time is preferably 1~20h.
[0028] In the present invention, the carbonization temperature is preferably 600-1400°C, more preferably 1100-1300°C, and further preferably 1200-1300°C. The holding time is preferably 0.5-5h, more preferably 2-3h. The heating rate to the carbonization temperature is preferably 1-5°C / min, more preferably 2-5°C / min. The carbonization is preferably carried out in a high-temperature rotary kiln. After the carbonization, the resin is coated on the surface of the primary carbon-coated silicon-carbon material to form a second carbon layer, and the second carbon layer contains conductive nano-carbon fillers.
[0029] The present invention combines a high-density gas-phase coating process with a low-cost liquid-phase coating process to form a uniform carbon coating layer on the porous carbon surface deposited with nano-silicon particles; the primary carbon coating formed by the gas-phase coating ensures the density of the coating, and the secondary carbon coating is carried out by a liquid-phase mixing method using a resin as a precursor to form a more uniform carbon coating layer on the surface of the silicon-carbon material, further reducing the specific surface area while moderately increasing the thickness of the carbon coating layer.
[0030] After the carbonization, the present invention also preferably cools the obtained material, and then grinds, screens and demagnetizes it in sequence to obtain the silicon-carbon material with the multi-layer coating structure. In the present invention, the grinding method is preferably ball milling, the ball milling speed is preferably 300-650 rpm, and the time is preferably 3-24 hours; the mesh number of the sieve used for the screening is preferably ≥300 mesh.
[0031] The present invention provides the use of the silicon-carbon material with a multilayer coating structure described in the above technical solution or the silicon-carbon material with a multilayer coating structure prepared by the preparation method described in the above technical solution as a negative electrode active material in a lithium-ion battery. In the present invention, the negative electrode material of the lithium-ion battery also includes a conductive agent and a binder. The present invention has no special requirements for the conductive agent and the binder, and the conductive agent and the binder familiar to those skilled in the art can be used; in an embodiment of the present invention, the conductive agent is conductive carbon black, the binder is polyacrylic acid, and the mass ratio of the silicon-carbon material with a multilayer coating structure to the conductive agent and the binder is 96:1:3. The present invention has no special requirements for the application method, and the application method familiar to those skilled in the art can be used. The silicon-carbon material with a multilayer coating structure provided by the present invention is applied to lithium-ion batteries as a negative electrode active material, and has excellent specific capacity, coulombic efficiency and cycle performance.
[0032] In order to further illustrate the present invention, the silicon-carbon material with a multi-layer coating structure provided by the present invention, its preparation method and application are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0033] Example 1 A silicon-carbon material with a multi-layer coating structure, the preparation steps are as follows: (S101) placing porous carbon in a reactor, and after the temperature is raised to 450° C., introducing a mixed gas of silicon source gas and inert gas and keeping the temperature for a period of time, so as to deposit nano-silicon particles in the pores and on the surface of the porous carbon; The porous carbon is resin-based porous carbon (model BAC-P, B&T New Materials Group Co., Ltd.), with a specific surface area of 1216 m 2 / g, average pore size 1.8nm, D 50 The particle size is 7.8 μm; the reactor is a high-temperature rotary furnace; the insulation time is 5 hours; the silicon source gas is monosilane, and the flow rate is 5 L / min; the inert gas is argon, and the flow rate is 10 L / min.
[0034] (S102) continuing to raise the temperature to 550° C., introducing a mixed gas of a carbon source gas and an inert gas and maintaining the temperature for a period of time, thereby obtaining a primary carbon-coated silicon-carbon material; The insulation time is 5h; the carbon source gas is ethylene, and the flow rate is 1L / min; the inert gas is argon, and the flow rate is 5L / min; The mass fraction of nano-silicon in the primary carbon-coated silicon-carbon material is 58.6%, the mass fraction of carbon is 41.4%, the average particle size of nano-silicon is 6.6nm, and the thickness of the primary carbon coating layer (ie, the first carbon layer) in the primary carbon-coated silicon-carbon material is 38nm.
[0035] (S103) stirring and mixing the primary carbon-coated silicon-carbon material and the resin dispersion, then evaporating the solvent and transferring the material to a high-temperature rotary kiln, heating the temperature to a specified temperature and keeping the temperature for a period of time to carbonize the resin, cooling the temperature, grinding, screening, and demagnetizing the material to obtain a secondary carbon-coated silicon-carbon material, i.e., the silicon-carbon material with a multi-layer coating structure; The resin dispersion is composed of phenolic resin, carbon nanotubes and a dispersant, wherein the dispersant is water and ethanol, and the volume ratio of water to ethanol is 4:1; the mass fraction of the phenolic resin in the resin dispersion is 4.0%, and the mass fraction of the carbon nanotubes in the dispersion is 0.4%; The mass ratio of the primary carbon-coated silicon-carbon material to the resin dispersion is 1:2, the stirring rate is 500 rpm, and the stirring time is 6 hours; the evaporation solvent is heated and evaporated at 100° C. under vacuum conditions for 20 hours; The carbonization temperature is 1100°C, the heating rate is 2°C / min, and the holding time is 2h; the thickness of the secondary carbon coating layer (i.e., the second carbon layer) is 90nm; the grinding method is ball milling, the ball milling rate is 450rpm, and the ball milling time is 6h; the mesh number of the sieve used in the screening process is 325 mesh; The average particle size of the multi-layer coated silicon-carbon material is 8.5 μm, and the specific surface area is 3.2 m 2 / g, microscopic morphology Figure 1 shown.
[0036] The multi-layer coated silicon-carbon material prepared in Example 1 was used as the negative electrode material to carry out electrochemical performance testing: Test method: The prepared multi-layer coated silicon-carbon material is used as the active material, and is mixed evenly with conductive carbon black SuperP and polyacrylic acid (PAA) in a mass ratio of 96:1:3. Ultrapure water is used as a dispersant to coat the slurry into an electrode sheet. The current collector is copper foil, and the active material loading is 2.5 g / cm 2 ; The electrode sheet was dried at 120°C in a vacuum drying oven for 12 h, and a silicon-carbon electrode sheet was obtained by rolling and punching; a metal lithium sheet was used as a counter electrode, 1 mol / L LiPF6 (EC:DEC=1:1) was used as an electrolyte, and the above silicon-carbon electrode sheets were assembled into button batteries in a glove box, and the charge and discharge performance tests were carried out.
[0037] Figure 2 The cycle specific capacity curve of the lithium-ion battery assembled with the silicon-carbon material of the multi-layer coating structure in Example 1, Figure 3 The charge and discharge curves of the lithium-ion battery assembled with the multi-layer coated silicon-carbon material in Example 1. The first specific capacity of the multi-layer coated silicon-carbon material prepared in Example 1 is 2071 mAh / g, the first efficiency (i.e., the first coulomb efficiency) is 93.3%, and the capacity retention rate after 100 cycles is 97.4%.
[0038] Example 2 A silicon-carbon material with a multi-layer coating structure, the preparation steps are as follows: (S201) placing porous carbon in a reactor, and after the temperature is raised to 550° C., introducing a mixture of silicon source gas and inert gas and keeping the temperature for a period of time, so as to deposit nano-silicon particles in the pores and on the surface of the porous carbon; The porous carbon is biomass-based porous carbon (model SDPC-G1, Fujian Yuanli Activated Carbon Co., Ltd.) with a specific surface area of 1363 m 2 / g, average pore size is 2.0nm, D 50The particle size is 6.9 μm; the reactor is a high-temperature rotary furnace; the insulation time is 5 hours; the silicon source gas is disilane, and the flow rate is 3 L / min; the inert gas is argon, and the flow rate is 10 L / min.
[0039] (S202) continuing to raise the temperature to 650° C., introducing a mixed gas of a carbon source gas and an inert gas and maintaining the temperature for a period of time, thereby obtaining a primary carbon-coated silicon-carbon material; The holding time is 4 hours; the carbon source gas is acetylene, and the flow rate is 2 L / min; the inert gas is argon, and the flow rate is 10 L / min; The mass fraction of nano-silicon in the primary carbon-coated silicon-carbon material is 46.1%, the mass fraction of carbon is 53.9%, the average particle size of nano-silicon is 4.9 nm, and the thickness of the primary carbon coating layer (ie, the first carbon layer) in the primary carbon-coated silicon-carbon material is 72 nm.
[0040] (S203) stirring and mixing the primary carbon-coated silicon-carbon material and the resin dispersion, then evaporating the solvent and transferring the material to a high-temperature rotary kiln, heating the temperature to a specified temperature and keeping the temperature for a period of time to carbonize the resin, cooling the temperature, grinding, screening, and demagnetizing the material to obtain a secondary carbon-coated silicon-carbon material, i.e., the silicon-carbon material with a multi-layer coating structure; The resin dispersion consists of urea-formaldehyde resin, graphene and a dispersant, wherein the dispersant is acetone, the mass fraction of the urea-formaldehyde resin in the resin dispersion is 7.0%, and the mass fraction of the graphene in the resin dispersion is 0.7%; The mass ratio of the primary carbon-coated silicon-carbon material to the resin dispersion is 1:4, the stirring rate is 600 rpm, and the stirring time is 10 hours; the evaporation solvent is heated and evaporated at 80° C. under vacuum conditions for 8 hours; The carbonization temperature is 1200°C, the heating rate is 2°C / min, and the holding time is 3h; the thickness of the secondary carbon coating layer (i.e., the second carbon layer) is 166nm; the grinding method is ball milling, the ball milling rate is 550rpm, and the ball milling time is 8h; the mesh number of the sieve used in the screening process is 325 mesh; The average particle size of the silicon-carbon negative electrode material is 7.4 μm and the specific surface area is 4.4 m 2 / g.
[0041] The multi-layer coated silicon-carbon material prepared in Example 2 was used as the negative electrode material for electrochemical performance testing, and the testing method was the same as that in Example 1. Test results: The first specific capacity of the multi-layer coated silicon-carbon material prepared in Example 2 was 1986 mAh / g, the first efficiency was 92.6%, and the capacity retention rate after 100 cycles was 97.7%.
[0042] Example 3 A silicon-carbon material with a multi-layer coating structure, the preparation steps are as follows: (S301) placing porous carbon in a reactor, and after the temperature is raised to 550° C., introducing a mixed gas of silicon source gas and inert gas and keeping the temperature for a period of time, so as to deposit nano-silicon particles in the pores and on the surface of the porous carbon; The porous carbon is asphalt-based porous carbon (model MRP16, Changzhou Chuangming Super Electric Material Technology Co., Ltd.) with a specific surface area of 934 m 2 / g, average pore size is 2.5nm, D 50 The particle size is 6.3 μm; the reactor is a fluidized bed; the insulation time is 6 hours; the silicon source gas is trisilane, and the flow rate is 10 L / min; the inert gas is argon, and the flow rate is 25 L / min.
[0043] (S302) continuing to raise the temperature to 750° C., introducing a mixed gas of a carbon source gas and an inert gas and maintaining the temperature for a period of time, thereby obtaining a primary carbon-coated silicon-carbon material; The insulation time is 6 hours; the carbon source gas is propylene, and the flow rate is 5 L / min; the inert gas is argon, and the flow rate is 15 L / min; The mass fraction of nano-silicon in the primary carbon-coated silicon-carbon material is 61.5%, the mass fraction of carbon is 38.5%, the average particle size of nano-silicon is 8.7nm, and the thickness of the primary carbon coating layer (ie, the first carbon layer) in the primary carbon-coated silicon-carbon material is 91nm.
[0044] (S303) stirring and mixing the primary carbon-coated silicon-carbon material and the resin dispersion, then removing the solvent and transferring to a high-temperature rotary kiln, heating to a specified temperature and keeping the temperature for a period of time to carbonize the resin, cooling, grinding, screening, and demagnetizing to obtain a secondary carbon-coated silicon-carbon material, i.e., the silicon-carbon material with a multi-layer coating structure; The resin dispersion is composed of epoxy resin, carbon nanofibers and a dispersant; the dispersant is tetrahydrofuran; the mass fraction of the epoxy resin in the resin dispersion is 8%, and the mass fraction of the carbon nanofibers in the resin dispersion is 0.5%; The mass ratio of the primary carbon-coated silicon-carbon material to the resin dispersion is 1:5, the stirring rate is 1000 rpm, and the stirring time is 15 hours; the solvent removal is freeze-drying at -50°C under vacuum for 12 hours; The carbonization temperature is 1300°C, the heating rate is 5°C / min, and the holding time is 3h; the thickness of the secondary carbon coating layer (i.e., the second carbon layer) is 183nm; the grinding method is ball milling, the ball milling rate is 650rpm, and the ball milling time is 6h; the mesh size of the sieve used in the screening process is 500 mesh; The average particle size of the multi-layer coated silicon-carbon material is 6.7 μm, and the specific surface area is 3.1 m 2 / g.
[0045] The multi-layer coated silicon-carbon material prepared in Example 3 was used as the negative electrode material for electrochemical performance testing, and the testing method was the same as that in Example 1. Test results: The first specific capacity of the multi-layer coated silicon-carbon material prepared in Example 3 was 1882 mAh / g, the first efficiency was 94.1%, and the capacity retention rate after 100 cycles was 95.3%.
[0046] Comparative Example 1 A silicon-carbon material, the preparation steps are as follows: (S401) placing porous carbon in a reactor, and after the temperature is raised to 450° C., introducing a mixed gas of a silicon source gas and an inert gas and keeping the temperature for a period of time, depositing nano-silicon particles in the pores and on the surface of the porous carbon, thereby obtaining porous carbon with deposited nano-silicon; The porous carbon is resin-based porous carbon (model BAC-P, B&T New Materials Group Co., Ltd.), with a specific surface area of 1216 m 2 / g, average pore size 1.8nm, D 50 The particle size is 7.8 μm; the reactor is a high-temperature rotary furnace; the holding time is 5 h; the silicon source gas is monosilane, and the flow rate is 5 L / min; the inert gas is argon, and the flow rate is 10 L / min; The mass fraction of nano-silicon in the porous carbon deposited with nano-silicon is 73.1%, and the mass fraction of carbon is 26.9%.
[0047] (S402) mixing the porous carbon with deposited nano-silicon obtained in step (S401) with a resin dispersion, then evaporating the solvent and transferring the mixture to a high-temperature rotary kiln, heating the mixture to a specified temperature and keeping the temperature for a period of time to carbonize the resin, and then grinding, screening, and demagnetizing the mixture after carbonization and cooling to obtain a silicon-carbon material (primary carbon coating); The resin dispersion is composed of phenolic resin, carbon nanotubes and a dispersant, wherein the dispersant is water and ethanol, and the volume ratio of water to ethanol is 4:1; the mass fraction of the resin in the resin dispersion is 4.0%; the mass fraction of the carbon nanotubes in the resin dispersion is 0.4%; The mass ratio of the porous carbon deposited with nano-silicon to the resin dispersion is 1:2, the stirring rate is 500 rpm, and the stirring time is 6 hours; the evaporation solvent is heated and evaporated at 100° C. under vacuum conditions for 20 hours; The carbonization temperature is 1100°C, the heating rate is 2°C / min, and the holding time is 2h; the thickness of the carbon coating layer is 82nm; the grinding method is ball milling, the ball milling rate is 450rpm, and the ball milling time is 6h; the mesh number of the sieve used in the screening process is 325 mesh; The average particle size of the silicon-carbon material (primary carbon coating) is 8.1 μm, and the specific surface area is 3.9 m 2 / g.
[0048] The silicon-carbon material (carbon-coated once) prepared in Comparative Example 1 was used as the negative electrode material for electrochemical performance testing, and the testing method was the same as that in Example 1. Test results: The silicon-carbon material (carbon-coated once) prepared in Comparative Example 1 had an initial specific capacity of 2052 mAh / g, an initial efficiency of 90.2%, and a capacity retention rate of 71.4% after 100 cycles.
[0049] Comparative Example 2 A silicon-carbon material, the preparation steps are as follows: (S501) placing porous carbon in a reactor, and after the temperature is raised to 450° C., introducing a mixed gas of silicon source gas and inert gas and keeping the temperature for a period of time, so as to deposit nano-silicon particles in the pores and on the surface of the porous carbon; The porous carbon is resin-based porous carbon (model BAC-P, B&T New Materials Group Co., Ltd.), with a specific surface area of 1216 m 2 / g, average pore size 1.8nm, D 50 The particle size is 7.8 μm; the reactor is a high-temperature rotary furnace; the insulation time is 5 hours; the silicon source gas is monosilane, and the flow rate is 5 L / min; the inert gas is argon, and the flow rate is 10 L / min.
[0050] (S502) continuing to raise the temperature to 550°C, introducing a mixed gas of a carbon source gas and an inert gas and keeping the temperature for a period of time to obtain a primary carbon-coated silicon-carbon material; The insulation time is 5h; the carbon source gas is ethylene, and the flow rate is 1L / min; the inert gas is argon, and the flow rate is 5L / min; The mass fraction of nano-silicon in the primary carbon-coated silicon-carbon material is 58.1%, the mass fraction of carbon is 41.9%, and the thickness of the primary carbon coating layer in the primary carbon-coated silicon-carbon material is 36 nm.
[0051] (S503) stirring and mixing the primary carbon-coated silicon-carbon material and the resin dispersion, then evaporating the solvent and transferring the material to a high-temperature rotary kiln, heating the material to a specified temperature and keeping the temperature for a period of time to carbonize the resin, cooling the material, grinding, screening, and demagnetizing the material to obtain a secondary carbon-coated silicon-carbon material; The resin dispersion is composed of phenolic resin and a dispersant, wherein the dispersant is water and ethanol, and the volume ratio of water to ethanol is 4:1; the mass fraction of the phenolic resin in the resin dispersion is 4.0%; The mass ratio of the primary carbon-coated silicon-carbon material to the resin dispersion is 1:2, the stirring rate is 500 rpm, and the stirring time is 6 hours; the evaporation solvent is heated and evaporated at 100° C. under vacuum conditions for 20 hours; The carbonization temperature is 1100°C, the heating rate is 2°C / min, and the holding time is 2h; the thickness of the secondary carbon coating layer is 94nm; the grinding method is ball milling, the ball milling rate is 450rpm, and the ball milling time is 6h; the mesh number of the sieve used in the screening process is 325 mesh; The average particle size of the secondary carbon-coated silicon-carbon material is 8.4 μm, and the specific surface area is 3.5 m 2 / g.
[0052] The secondary carbon-coated silicon-carbon material prepared in Comparative Example 2 was used as the negative electrode material for electrochemical performance testing, and the testing method was the same as that in Example 1. Test results: The first specific capacity of the secondary carbon-coated silicon-carbon material prepared in Comparative Example 2 was 1708 mAh / g, the first efficiency was 93.1%, and the capacity retention rate after 100 cycles was 95.4%.
[0053] Comparative Example 3 A silicon-carbon material, the preparation steps are as follows: (S601) placing nano-silicon in a reactor, raising the temperature to 550° C., introducing a mixed gas of a carbon source gas and an inert gas and keeping the temperature for a period of time to obtain a primary carbon-coated silicon-carbon product; The D of the nano-silicon 50 The particle size is 70nm, the reactor is a high-temperature rotary furnace; the insulation time is 5h; the carbon source gas is ethylene, and the flow rate is 1L / min; the inert gas is argon, and the flow rate is 5L / min; The mass fraction of nano-silicon in the primary carbon-coated silicon-carbon product is 76.8%, the mass fraction of carbon is 23.2%, and the thickness of the primary carbon coating layer is 36 nm.
[0054] (S602) stirring and mixing the primary carbon-coated silicon-carbon product with the resin dispersion, then evaporating the solvent and transferring to a high-temperature rotary kiln, heating to a specified temperature and keeping the temperature for a period of time to carbonize the resin, cooling, grinding, screening, and demagnetizing to obtain a secondary carbon-coated silicon-carbon material; The resin dispersion is composed of phenolic resin, carbon nanotubes and a dispersant, wherein the dispersant is water and ethanol, and the volume ratio of water to ethanol is 4:1; the mass fraction of the phenolic resin in the resin dispersion is 4.0%, and the mass fraction of the carbon nanotubes in the resin dispersion is 0.4%; The mass ratio of the once coated silicon-carbon product to the resin dispersion is 1:2, the stirring rate is 500 rpm, and the stirring time is 6 hours; the evaporating solvent is heated and evaporated at 100° C. under vacuum conditions for 20 hours; The carbonization temperature is 1100°C, the heating rate is 2°C / min, and the holding time is 2h; the thickness of the secondary carbon coating layer is 89nm; the grinding method is ball milling, the ball milling rate is 450rpm, and the ball milling time is 6h; the mesh number of the sieve used in the screening process is 325 mesh; The average particle size of the secondary carbon-coated silicon-carbon material is 8.5 μm, and the specific surface area is 3.2 m 2 / g.
[0055] The secondary carbon-coated silicon-carbon material prepared in Comparative Example 3 was used as the negative electrode material for electrochemical performance testing, and the testing method was the same as that in Example 1. Test results: The first specific capacity of the secondary carbon-coated silicon-carbon material prepared in Comparative Example 3 was 1655 mAh / g, the first efficiency was 71.9%, and the capacity retention rate after 100 cycles was 73.3%.
[0056] The battery performance test results of the silicon-carbon materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 as negative electrodes are listed in Table 1.
[0057] Table 1 Battery performance test results of silicon-carbon negative electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3
[0058] As can be seen from Table 1, the silicon-carbon material prepared in the embodiment of the present invention has good cycle performance, first reversible capacity and first efficiency. In Comparative Example 1, the porous carbon silicon is directly coated with resin after deposition, and a dense carbon coating layer fails to form on the surface of the silicon particles. The resin carbon coating alone is difficult to suppress the volume expansion effect of the silicon particles, and the nano silicon particles are easily exposed after mechanical grinding, resulting in reduced cycle performance. In Comparative Example 2, no conductive nano carbon material is added to the resin dispersion for secondary coating of the silicon carbon material, and the conductivity of the obtained carbon coating layer is reduced, and the interface impedance and polarization effect are improved, resulting in a reduction in reversible capacity. In Comparative Example 3, the silicon material used is ground nano silicon rather than vapor deposited nano silicon, the particle size is relatively larger, the expansion effect is more significant, and there is no porous carbon carrier to provide a buffer space, and the first reversible capacity, coulombic efficiency and cycle stability are significantly reduced.
[0059] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A silicon-carbon material with a multi-layer coating structure, characterized in that: The porous carbon core comprises a first carbon layer and a second carbon layer which sequentially cover the porous carbon core from the inside out, wherein the porous carbon core comprises porous carbon and nano-silicon particles deposited on the surface and in the pores of the porous carbon, and the pores of the porous carbon comprise micropores; and conductive nano-carbon fillers are dispersed in the second carbon layer.
2. The multi-layered silicon-carbon material according to claim 1, characterized in that: The porous carbon includes one or more of biomass-based porous carbon, resin-based porous carbon and asphalt-based porous carbon; the specific surface area of the porous carbon is 700-1900m 2 / g, average pore size is 0.5~5nm, D 50 The particle size is 2~15μm.
3. The multi-layered silicon-carbon material according to claim 1, characterized in that: The thickness of the first carbon layer is 10-500 nm; the thickness of the second carbon layer is 20-500 nm.
4. The silicon-carbon material with a multi-layer coating structure according to any one of claims 1 to 3, characterized in that: The particle size of the nano silicon particles is 2-10 nm; the mass of the nano silicon particles is 30-70% of the total mass of the porous carbon core and the first carbon layer.
5. The silicon-carbon material with a multi-layer coating structure according to claim 1, characterized in that: The conductive nano-carbon filler includes one or more of graphene, carbon nanotubes, nano-carbon black and nano-carbon fibers; the mass content of the conductive nano-carbon filler in the second carbon layer is 3-15%.
6. The silicon-carbon material with a multi-layer coating structure according to claim 1, characterized in that: The specific surface area of the silicon-carbon material of the multi-layer coating structure is less than 5.5m 2 / g.
7. The method for preparing the multi-layer coated silicon-carbon material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The porous carbon is subjected to a first chemical vapor deposition under the condition of introducing a silicon source gas and a first inert gas, so as to form nano silicon particles on the surface and in the pores of the porous carbon, thereby obtaining the porous carbon core; the temperature of the first chemical vapor deposition is 300-550° C.; The porous carbon core body is subjected to a second chemical vapor deposition under the condition of introducing a carbon source gas and a second inert gas, so as to form a first carbon layer on the surface of the porous carbon core body to obtain a primary carbon-coated silicon-carbon material; the temperature of the second chemical vapor deposition is 450-750° C.; The primary carbon-coated silicon-carbon material is mixed with a resin dispersion, and the solvent is removed and carbonized in sequence to form a second carbon layer on the outer surface of the first carbon layer to obtain the silicon-carbon material with a multi-layer coating structure; the resin dispersion includes a resin, a conductive nano-carbon filler and a dispersant.
8. The preparation method according to claim 7, characterized in that: The silicon source gas includes one or more of monosilane, disilane, trisilane, butasilane and dichlorosilane, and the flow rate of the silicon source gas is 1~15L / min; the first inert gas includes nitrogen and / or argon, and the flow rate of the first inert gas is 1~30L / min.
9. The preparation method according to claim 7, characterized in that: The carbon source gas includes one or more of methane, ethane, propane, cyclohexane, ethylene, propylene and acetylene, and the flow rate of the carbon source gas is 0.5~5L / min; the second inert gas includes nitrogen and / or argon, and the flow rate of the second inert gas is 1~20L / min.
10. Use of the multi-layer coated silicon-carbon material according to any one of claims 1 to 6 or the multi-layer coated silicon-carbon material prepared by the preparation method according to any one of claims 7 to 9 as a negative electrode active material in a lithium ion battery.
Citation Information
Patent Citations
Carbon-silicon negative electrode material and preparation method thereof
CN112054171A
Soft carbon-hard carbon-silicon composite negative electrode material and preparation method thereof
CN115360334A
Low-expansion silicon-carbon negative electrode material and preparation method thereof
CN115986075A
Silicon-carbon negative electrode material, preparation method thereof and lithium ion battery
CN116799178A
Silicon-carbon composite material, preparation method thereof and secondary battery
CN117790730A
Cited By
Silicon-carbon-based composite material, preparation method and application of silicon-carbon-based composite material in lithium ion battery
CN120072918A
One-core dual-coated battery positive electrode material, preparation method and battery
CN120565650A
Silicon-carbon negative electrode material, preparation method and application thereof, and battery negative electrode
CN120933333A